Порівняльний аналіз похованих та зональних ґрунтів як метод реконструкції палеогеографічних обстановок голоцену - Мацібора, О.В. (Український географічний журнал, 2011)
Проведен сравнительный анализ погребенных и зональных почв голоцена в северной части степной зоны Украины. Исследовались карбонатный и гумусовый профили почв, а также особенности их генезиса. Установлены общие тренды эволюции почв для исследуемой территории на протяжении последних 3500 лет. На основании изученных почвенных параметров были проведены палеогеографические реконструкции природных условий второй половины суббореального периода голоцена. The comparative analysis of the buried and zonal Holocene soils in the steppe zone of Ukraine has been carried out. The genesis of the soils, their carbonate and humus profiles have been investigated. The trends of soils evolution on the territory during last 3500 years have been determined. The palaeogeographical reconstructions of the natural conditions during the second half of subboreal period of Holocene have been created on the basis of the made soil investigations.